Competition and well-being: Does market competition make people unhappy? - Justina A. V. Fischer (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
Empirical research on the role of economic institutions for subjective well-being is still widely lacking, while recent economic-experimental outcomes suggest that experienced utility may depend on the intensity of market competition. This paper is the first to empirically analyze the implication of market competition for subjective well-being using real-life survey data on 80,000 individuals in more than 60 countries from the World Values Survey 1997-2001. In support of our hypothesis, we find that market competition aggravates the impact of individual's bargaining position in economic transactions on her subjective well-being - compared to the least powerful in society. Put differently, we find that market competition enlarges the happiness differences caused by cleavages in socio-economic position. Our results also suggest that competition induced welfare changes are not gender-specific, while a stronger rule of law appears to prevent the generation of such additional benefits or losses. Particularly the latter results call for further economic-experimental corroboration in the laboratory, but also bear important policy implications.
Keywords: C99; D02; D40; I31; 330; Subjective well-being; happiness; utility; competition; rule of law; completeness of contract; laboratory experiment; World Values Survey; Zufriedenheit; Lebensqualität; Wettbewerb; Marktstruktur; Rechtsstaat; Welt